1993
DOI: 10.2527/1993.7113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing on the comparative feeding value of barley for feedlot cattle

Abstract: Ninety-six crossbred steers were used in a 172-d feedlot growth performance trial to determine the effects of type processing on the comparative feeding value of barley in a 90% concentrate finishing diet. Treatments were: 1) steam-flaked corn (SFC; density = .31 kg/L); 2) dry-rolled barley (DRB; density = .39 kg/L); 3) steam-rolled barley, coarse roll (SRB-C, density = .39 kg/L); and 4) SRB, thin roll (SRB-T, density = .19 kg/L). The ADG was similar (P > .10) across barley treatments, averaging 1.29 kg/d. Fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
38
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 17 publications
20
38
5
Order By: Relevance
“…Calculated barley NE m and NE g contents ranged from 8.94 to 9.51 and 5.98 to 6.55 MJ kg -1 OM, respectively. These values are in the range reported by NRC (1984NRC ( , 1986 and Zinn (1993), but less than those reported by Boss and Bowman (1996) when expressed on an OM basis.…”
Section: Trialcontrasting
confidence: 56%
See 1 more Smart Citation
“…Calculated barley NE m and NE g contents ranged from 8.94 to 9.51 and 5.98 to 6.55 MJ kg -1 OM, respectively. These values are in the range reported by NRC (1984NRC ( , 1986 and Zinn (1993), but less than those reported by Boss and Bowman (1996) when expressed on an OM basis.…”
Section: Trialcontrasting
confidence: 56%
“…These values are in the range reported by Zinn (1993) and Boss and Bowman (1996), but greater than those reported by NRC (1984NRC ( , 1996 when expressed on an OM basis.…”
Section: Trialcontrasting
confidence: 44%
“…However, an increasing level of SFT substitution for SFC decreased digestion of organic matter (OM) (linear component, P = .03) and ADF (linear component, P < .01), but tended to increase apparent N digestion (P = .09). Consistently SFC has shown lower total tract N digestion than SFW (Zinn 1992) and SFB (Zinn 1993). This latter effect is expected due to the increasing level of dietary N brought about by the replacement (NRC 1985).…”
Section: Trialsupporting
confidence: 50%
“…Using the replacement technique, the NE m value of SFT can be determined as follows: NE m SFT = 2.38-(NE m basal plus SFC diet-NE m basal plus SFT diet)/0.60, where 2.38 is the tabular (Zinn 1993), corn (Zinn et al 1998), and sorghum (Zinn et al 2008b). …”
Section: Trialmentioning
confidence: 99%
“…Zinn (1993) reported that cattle fed steam-flaked corn ate less and gained less than calves fed dry or steam-rolled barley. In most reports, however, feed intake and growth rate of feedlot cattle fed high grain barley diets were similar (Nichols and Weber 1988; Bradshaw et al 1992;Mathison and Engstrom 1995;Milner et al 1995;Owens et al 1995), or lower (Boss et al 1994;Boss and Bowman 1996) than for calves fed corn.…”
Section: Cattle Performancementioning
confidence: 99%